Carbon emissions reduction in shipping based on four-party evolutionary game - Suyong Zhang; Xiyan Song (Frontiers in Marine Science)
In order to realize a win-win situation between economic development and environmental benefits, this paper constructs a four-party evolutionary game model including the government, two homogeneous ports and shipping companies based on evolutionary game theory. By calculating the payoff matrices of the four parties and replicating the dynamic equations, according to the Jacobi matrix, we study and discuss the possible stabilization points of the model under five different scenarios. The game is simulated using MATLAB and the relevant parameters are selected for sensitivity analysis. The results show that the environmental benefits are maximized when the government does not implement the policy and the port and shipping companies use the shore electricty system (i.e., the stability point E12 (0,1,1,1)). Meanwhile, by analyzing the port size sensitivity, when t=1.116, the large-scale port evolution tends to 0, while the small-scale port fluctuates up and down, which leads to the conclusion that the small-scale ports have more potential to implement shore electricty and are able to gain benefits faster. This study provides theoretical support for the implementation of shore electricty systems, while pointing out the key role of the government in promoting the development of shore electricty. It provides a reference for effectively promoting the use of shore electricty in the context of carbon emission reduction, which is especially important for the implementation of shore electricty in small-scale ports and helps to maximize the environmental benefits of port operations.